Parque industrial ecoeficiente del cuero (PIEC): Para la actividad curtiembre localizada en el barrio San Benito de Bogotá, como elemento urbano que busca mitigar el impacto ambiental causado por los procesos industriales. - Farfán Zapata, Simón Camilo (Universidad Antonio Nariño, 2022)
In the San Benito neighborhood of the city of Bogotá, a group of companies dedicated to the leather industry, the tanneries, is located. Being this activity one of the most polluting of the green landscape, and mainly of the Tunjuelo river, due to its chemical discharges, thus affecting the quality of life of the inhabitants of the sector. The new global industry treaties propose the responsible use of resources by adopting strategies and technologies that manage to mitigate the environmental impact generated by waste.